INDEKS BUDAYA KERJA DALAM PELAYANAN PERNIKAHAN DI KABUPATEN BANYUMAS - Rosidin Rosidin (Jurnal Dialog, 2016)
This study reports the work culture of marriage service personnel in Banyumas and analyses which aspects of service should be prioritized for improvement. This study employs a quantitative approach by using survey. The total sample of 140 was gained using purposive random sampling. The validity and reliability of instruments indicated that the 25 question items are valid and reliable. The study found out that (1) the index of work culture showed 75,77 which can be categorized as ‘good’, (2) all aspects of work culture (e.g. integrity, professionalism, innovation, responsibility, and exemplary) did not fall into ‘very good’ category which mean that the service is not satisfactory, (3) the lowest criteria of work culture was found in integrity aspect (63,85 = not good enough). Therefore, integrity is the aspect of work culture which needs to be prioritized for the improvement. KEY WORDS: Integrity, professional, innovative, responsible, exemplary, work culture, marriage service